2011
DOI: 10.1371/journal.ppat.1002284
|View full text |Cite
|
Sign up to set email alerts
|

Noninfectious Retrovirus Particles Drive the Apobec3/Rfv3 Dependent Neutralizing Antibody Response

Abstract: Members of the APOBEC3 family of deoxycytidine deaminases counteract a broad range of retroviruses in vitro through an indirect mechanism that requires virion incorporation and inhibition of reverse transcription and/or hypermutation of minus strand transcripts in the next target cell. The selective advantage to the host of this indirect restriction mechanism remains unclear, but valuable insights may be gained by studying APOBEC3 function in vivo. Apobec3 was previously shown to encode Rfv3, a classical resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(76 citation statements)
references
References 69 publications
(122 reference statements)
3
72
0
1
Order By: Relevance
“…At 7 dpi, the percentages of infected bone marrow cells were evaluated by flow cytometry using a monoclonal antibody (MAb) against the FV glyco-gag protein (Fig. 1A) (19). Compared to control sera from uninfected mice, mA3 ϩ/s antisera conferred significant protection, whereas mA3 Ϫ/s antisera did not (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…At 7 dpi, the percentages of infected bone marrow cells were evaluated by flow cytometry using a monoclonal antibody (MAb) against the FV glyco-gag protein (Fig. 1A) (19). Compared to control sera from uninfected mice, mA3 ϩ/s antisera conferred significant protection, whereas mA3 Ϫ/s antisera did not (Fig.…”
mentioning
confidence: 99%
“…2A). To test if infected mA3 ϩ/s mice produce higher titers of FV-specific IgG2 antibodies, we quantified virus-specific titers of the different isotypes and IgG subclasses by endpoint titration enzyme-linked immunosorbent assay (ELISA) (19). mA3 ϩ/s mice produced higher levels of virus-specific IgG2 against native virions than mA3 Ϫ/s mice but similar IgG1, IgG3, and IgM titers (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Par ailleurs, les virus défectifs interférents bloquent la réplication des virus infectieux, notamment en réquisitionnant la polymé-rase virale et d'autres facteurs pour leur propre réplication [3]. En outre, des particules rétrovirales non infectieuses contenant des génomes mutants générés par l'action de déoxycytidines déaminases -facteurs de restriction comme par exemple APOBEC3 -ont la capacité d'induire une réponse neutralisante, ce qui contribue au contrôle de la charge virale in vivo [16]. La majorité des virus codent pour des protéines qui bloquent la réponse antivirale dans les cellules qu'ils infectent (Figure 1).…”
Section: Rôle Fonctionnel Des Particules Virales Incomplètesunclassified
“…Although exogenous murine leukemia viruses (MuLVs) are relatively insensitive to the actions of mA3 (2-7), several studies have reported partial inhibition of exogenous MuLVs after incorporation of mA3 (2,3,6,(8)(9)(10)(11). Furthermore, the finding that Rfv3, a resistance gene for Friend erythroleukemia, encodes mA3 and is responsible for a decreased infectious titer of the Friend MuLV (Fr-MuLV) (11)(12)(13) strongly suggests that mA3 inhibits the replication of exogenous MuLVs in vivo. Exogenous ecotropic MuLVs, such as the FrMuLV and Moloney MuLV (Mo-MuLV), are inhibited through mechanisms that do not appear to involve cytidine deamination (2,9,10).…”
mentioning
confidence: 99%